Nanopartículas de hidróxido de cálcio suportadas em carvão ativado do endocarpo de macaúba para desacidificação de óleos vegetais - Marcos Roberto do Nascimento Pereira (2018)
Several studies are being developed trying to find possible alternatives for adsorption of urea and deacidification of vegetable oils. In this scenario, activated carbons (ACs) are considered promising materials due to their unique properties, such as high specific surface area and large pore volume, being applied directly as adsorbents or supports in production of composites. Thus, in the first approach, this study shows the potential use of macauba endocarp as raw material for the ACs production. ACs were prepared using physical activation by CO2 at different temperatures (700-850°C) and residence times (1-4 h). The obtained ACs showed high surface area (990-1645 m2 g-1) and micropores volumes fractions above 85%. Sequentially, the adsorption tests of urea were carried out using the ACs. The results showed removal capacities of urea of 28-68 mg per g of AC. The study showed that the adsorption of urea is directly related to the mesoporosity obtained of the ACs. Sequentially, the adsorption tests of oleic acid (OA) mixed with soybean oil were carried out by using the porous adsorbents MCM-41 and ACs derived from macauba endocarp. The materials MCM-41 and ACs proved to be inefficient for the removal of acid oleic from soybean oil through adsorption process. Calcium hydroxide nanoparticles - Ca(OH)2NPs - were prepared in the presence of ethylene glycol, producing hexagonal nanocrystals with average size in the range of 126-490 nm. The use of Ca(OH)2NPs and commercial Ca(OH)2 was studied in tests the removal of OA in a mixture containing 20 wt% of oleic acid in soybean. The maximum OA removal capacities were of 6.0 and 4.4 mg per mg of Ca(OH)2NPs and Ca(OH)2, respectively. However, in these removal tests, only small volumes of soybean oiloleic acid were recovered from the original mixtures. Ca(OH)2NPs were supported on AC and MCM-41 matrixes yielding Ca(OH)2NPs/AC and Ca(OH)2NPs/MCM-41 composites, which were also tested towards OA removal. The composites Ca(OH)2NPs/MCM-41 and Ca(OH)2NPs/AC showed maximum OA removal capacities of 5.6 mg and 7.1 mg per mg of Ca(OH)2NPs, respectively, and about 90% of the mixtures of soybean oil-oleic acid were recovered from the initial mixture.In addition, biodiesel production was studied through transesterification of mixtures containing 5 and 10 wt% of oleic acid in soybean oil, previously deacidificated by Ca(OH)2NPs/AC composite. In these tests NaOH was used as catalyst. The results showed that by adding Ca(OH)2NPs/AC in mixtures soybean oiloleic acid and stirred at room temperature, then NaOH can be added directly to produce methyl esters with near 100% yield and easy phase separation of methyl esters, glycerol and calcium dioleate/Ca(OH)2NPs/AC